Motor plasticity after extra–intracranial bypass surgery in occlusive cerebrovascular disease. (5th July 2016) - Jussen, Daniel; Zdunczyk, Anna; Schmidt, Sein; Rösler, Judith; Buchert, Ralph; Julkunen, Petro; Karhu, Jari; Brandt, Stephan; Picht, Thomas; Vajkoczy, Peter
Abstract : Objective: To explore plasticity in patients scheduled for extra-intracranial bypass surgery due to unilateral symptomatic occlusive cerebrovascular disease via navigated transcranial magnetic stimulation. Methods: In this observational study, patients were allocated to different substudies and examined before and 3 months after operation. (1) Corticospinal excitability was determined via identification of the resting motor threshold. (2) Intracortical inhibition and facilitation were tested by paired pulse transcranial magnetic stimulation. (3) Area of cortical representation of the first dorsal interosseous muscle was identified. Results: (1) Resting motor thresholds were higher in the affected hemispheres with impaired cerebrovascular reserve capacity compared to the unaffected hemispheres (45.7% ± 2.2% compared to 39.2% ± 1.4%, n = 39, p < 0.05). Reduced excitability normalized 3 months after revascularization (51% ± 2.6% → 45% ± 1.9%, n = 21, p < 0.05). (2) In paired pulse paradigms, there was a motor disinhibition in the operated hemispheres. (3) There was a reduction of the cortical representation areas of the first dorsal interosseous muscle (2.3 ± 0.5 cm 2 → 0.9 ± 0.6 cm 2, n = 9, p < 0.05) after operation. Conclusions: Our data demonstrate a reversibly impaired motor cortical function in the chronically ischemic brain. In carefully selected patients, cerebral revascularization leads to improved motor output indicated by a lower resting motor threshold, intracortical disinhibition, and more focused motor cortical representation.